Application of Computer-Simulation-Based Clinical Case Training for General Practice Clinical Reasoning in Standardized Residency Training: A Digital Health Communication Perspective - Huan Yu; Zhen Qiao; Lina Ma; Peng Li (Review of Communication Research, 2026)
Clinical reasoning is a core competency in standardized residency training for general practitioners, yet conventional case-based instruction is often constrained by limited clinical exposure, inconsistent case complexity, and insufficient opportunities for repeated decision-making practice. This study explores the application of computer-simulation-based clinical case training to improve clinical reasoning among general practice residents from a digital health communication perspective. A digital simulation environment was designed to present interactive clinical cases integrating patient history, symptoms, examination findings, laboratory results, and dynamic clinical feedback. Residents were required to collect information, identify clinical problems, formulate differential diagnoses, select appropriate examinations, and develop management plans through sequential decision-making processes. The digital platform also supported real-time feedback, standardized communication pathways, and repeated case-based learning, enabling trainees to review their reasoning processes and identify decision-making errors. The effectiveness of the training approach was evaluated by comparing clinical reasoning performance, diagnostic accuracy, decision-making efficiency, and learner engagement before and after the intervention. The findings indicate that computer-simulation-based clinical case training can provide a structured, interactive, and repeatable learning environment that supports the development of diagnostic and clinical decision-making abilities. From the perspective of digital health communication, the approach also facilitates more effective information exchange, feedback delivery, and interaction between learners and simulated clinical scenarios. This study suggests that computer-simulation-based training may serve as a valuable supplementary strategy for enhancing clinical reasoning and digital competency in standardized general practice residency training.